MELATONIN AND QUERCETIN IMPROVE DEPRESSIVE-LIKE BEHAVIOR AND DYSLIPIDEMIA IN STREPTOZOTOCIN-INDUCED DIABETES IN RATS - Redouane Rebai; Abdennacer Boudah; Nesrine Derri (Journal of Animal and Plant Sciences, 2017)
This study was performed to examine and assess the beneficial effects of melatonin and quercetin on depressive disorders and the disturbance of lipid metabolism caused by diabetes mellitus. Diabetes was induced in male rats via intraperitoneal streptozotocin injection (70 mg/kg). Experiments were performed 72 h later. Diabetic rats were treated with melatonin or quercetin during 4 weeks. The anxiolytic and antidepressant-like effects of these two drugs were investigated in the last week of experiment, using the open-field and forced swimming tests. In the last day of the study, plasma insulin and lipid profile were determined in different experimental groups. Treatment with melatonin or quercetin significantly ameliorated anxiety-like and depressive-like behaviors. Furthermore, both melatonin and quercetin reversed the aspects of dyslipidemia observed in rats with diabetes, but the effect of the melatonin was more potent than quercetin, considering the dose used during this study.
Keywords: Diabetes; Melatonin; Quercetin; Mood disorders; Lipid profile